The state and prospects of the development of trilingual education in higher schools of Kazakhstan (on the example of Kaz NMU after S. Asfendiyarov) (Eurasian Journal of Philology Science and Education, 2016)
One of priorities of modern educational policyin the Republic of Kazakhstan is introduction a trekhjyazychiya (possession of three languages). Mastering Kazakh, Russian and English languages promotes formation notonly professional mobility, but also a competitiveness of modern citizens. The task of this article is to show the main directions of development of the program of trilingualtraining in KAZNMU for 20142020. Introduction of this program can be realized during the solution of such tasks as the analysis of conditions and opportunities of a modern education system in KAZNMU for realization of ideas of trinity of languages; definition of the priority directions of development of polylingual education. Along with it educational and methodical complexes which contain: training programs, textbooks, manuals, trilingual terminological glossaries, dictionaries, and also multimedia resources, are revised provisions of scientific students research, work of educational departments, committee of educational programs and library on ensuring educational process of departments/modules of university with educational literature in English and a state language is coordinated, active part in formation of the application for educational and methodical literature in the English and state languages is taken.
Keywords: polylingualism; language policy; trilingual education